Waldenstrom’s Macroglobulinemia: A Report of Two Cases, One with Severe Retinopathy and One with Renal Failure - Kudo, Naoko; Usui, Masakatsu; Nakabo, Yukiharu; Yoshida, Ken-ichi; Miki, Kenji; Osafune, Takashi; Nishimura, Keisuke; Imashuku, Shinsaku (Case Reports in Hematology, 2017)
We report here two cases of Waldenstrom’s macroglobulinemia (WM), one with central nervous system (CNS) symptoms and severe retinopathy and one with renal failure. In both cases, the serum IgM levels exceeded 3,000 mg/dL and monoclonal IgM-kappa was observed in the blood. At onset, Case 1, a 63-year-old female, developed CNS symptoms—namely, drowsiness and syncope. Case 2, a 58-year-old male, had nausea and dysgeusia on admission associated with renal failure, which is quite rare in patients with WM. Both patients exhibited hyperviscosity-related retinopathy, but it was particularly severe in Case 1: she suddenly lost her vision after admission. However, her vision recovered completely during treatment. Case 2 required hemodialysis immediately after admission. Needle biopsy of his kidney revealed tubulointerstitial nephritis with marked infiltration with CD20-positive lymphoplasmacytic lymphoma cells. After treatment, Case 1 has been in a remission longer than 8 years, but Case 2 died of pneumonia in 6 months. Since the initial symptoms of WM are ambiguous and vary significantly and hyperviscosity-related ophthalmological problems or severe renal dysfunction can arise, it is essential to promptly measure serum IgM levels and to institute appropriate care immediately when WM is confirmed in a patient.